Clinical aspects and management of inguinal endometriosis: A case series of 20 patients. Issue 10 (5th August 2019) - Arakawa, Tomoko; Hirata, Tetsuya; Koga, Kaori; Neriishi, Kazuaki; Fukuda, Shinya; Ma, Suke; Sun, Hui; Nagashima, Natsuki; Harada, Miyuki; Hirota, Yasushi; Wada‐Hiraike, Osamu; Fujii, Tomoyuki; et al.
Abstract: Aim: This study aimed to describe the clinical presentation, diagnostic evaluation, and operative or medical management of inguinal endometriosis. Methods: In this study, we retrospectively reviewed 20 cases of inguinal endometriosis in our facility, particularly on the clinical characteristics, diagnosis, and surgical and medical treatment. Results: We retrospectively investigated the following items for each patient: age at diagnosis, surgical history, presence of extragenital endometriosis, symptoms, imaging modalities, surgical therapy, hormonal therapy, follow‐up period, postoperative recurrence and time to recurrence. We identified 20 cases of inguinal endometriosis in our facility. First, 75% of the patients had right inguinal endometriosis. Second, T1‐weighted or fat‐saturated T1‐weighted images showed hyperintensity in the lesions in 17 patients (17/18 patients, 94.4%). Third, in 5 of 6 patients who underwent surgical therapy, we performed radical surgery to excise the inguinal lesion including the round ligament. One patient had disease relapse. Fourth, in 6 of 7 cases, dienogest effectively improved pain without significant adverse effects, but oral contraceptive was effective in 1 of 4 patients without significant adverse effects. Conclusion: We retrospectively reviewed 20 patients with inguinal endometriosis in our facility. We have shown that magnetic resonance imaging can be a useful imaging modality to obtain a specific diagnosis of this disease. In addition, inguinal endometriosis can be managed with radical surgery to resect lesions including the round ligament and with hormonal treatment. In particular, dienogest ameliorated symptoms, which can be an option for patients who do not want surgery.